Initial evaluations of the use of eugenol as an antioxidant in the in vitro maturation of ovine oocytes - Santos, Sara Rodrigues Pereira dos (2023)
The aim of this study was to assess the effect of eugenol on the in vitro production of ovine embryos. Oocytes were aspirated and taken for in vitro maturation (IVM), where they were divided into 4 groups: the CON (control), in which the oocytes were immersed in medium without an antioxidant; in the EU10, EU20, EU40 groups, the same medium as in the COM group was used, supplemented with 10, 20, and 40 µM of eugenol, respectively. The degree of expansion of cumulus cells was evaluated. Subsequently, the oocytes underwent in vitro fertilization and in vitro culture, and at the end of this process, the rate of cleaved structures was assessed. Regarding the expansion rate of cumulus cells, the CON group exhibited higher rates compared to the groups supplemented with eugenol. Evaluating oocytes with fully expanded cumulus cells, only the EU40 group showed a lower rate when compared to the rest of the treatment groups. Whereas observing oocytes with partially expanded cumulus cells, the EU40 group showed higher expansion percentages compared to the other treatments. Concerning the presence of the first polar body in the oocytes, it was observed that there was no statistical difference between the treatment groups. Lastly, concerning the cleaved structures, the CON and EU10 groups showed the highest rates compared to the EU20 and EU40 groups. Thus, it was possible to conclude that the use of 10 µM of eugenol in the IVM of ovine oocytes proved to be the optimal concentration of this substance.